How many common cranes (Grus grus) winter in Spain and Portugal? - Kees Woutersen (Munibe Ciencias Naturales)
The Iberian Peninsula, i.e., Spain and Portugal, is one of the most important wintering areas of common cranes (Grus grus), accounting for 50% of the European winter population. Historical winter censuses have never managed to provide a complete picture, and in 2015 a striking difference of almost 100.000 birds has been found between the winter census and an unprecedented census of migrating birds crossing the Pyrenees in spring after overwintering in the Iberian Peninsula. This infers that the Iberian wintering population is dramatically higher than annual winter censuses suggest. What lies behind this discrepancy in common crane numbers and how can we improve their population estimates? These underestimations of population size in winter censuses may be due to two reasons. Firstly, not all potential common crane winter areas have been covered, especially in the “dehesas” where access is often restricted. Secondly, a combination of different census methods (area counts vs. roost counts; and roost counts at dusk or at dawn) makes it difficult to achieve reliable results. In order to find those “missing” cranes and obtain a more realistic count of common cranes during winter, it would be necessary to make an additional effort, covering more areas and paying more attention to the census method. If these results fail to provide satisfactory results, attention should be shifted to key areas in order to monitor the demography of this emblematic species indirectly. RESUMEN: La Península Ibérica, España y Portugal, es una de las zonas de invernada más importantes de la grulla común (Grus grus), albergando alrededor del 50% de la población invernante europea. Los censos históricos de invierno nunca han podido ofrecer una imagen completa, y en 2015 se encontró una sorprendente diferencia de casi 100.000 aves entre el censo de invierno y un censo de aves migratorias que cruzan los Pirineos en primavera (algo que nunca se ha hecho antes), después de pasar el invierno en la Península Ibérica. Esto sugiere que la población invernante ibérica es mucho mayor de lo que indican los censos invernales anuales. La pregunta es por qué existe esta discrepancia en el número de grullas comunes y cómo podemos mejorar el conocimiento de su número. Los censos de invierno podrían subestimar el tamaño de la población por dos razones. En primer lugar, por no cubrir todas las posibles zonas de invernada de la grulla común, especialmente en las dehesas, donde el acceso suele estar restringido. En segundo lugar, una combinación de diferentes métodos de censo (censos de área vs. censos en dormidero; y censos de dormideros al anochecer o al amanecer) hace que sea difícil obtener resultados fiables. Para encontrar esas grullas que faltan y obtener un recuento más realista de las grullas comunes invernantes, sería necesario hacer un esfuerzo adicional, cubriendo más áreas y prestando más atención al método de censo. Si no se obtienen resultados satisfactorios, se debería centrar la atención en zonas clave para monitorear indirectamente la demografía de esta especie tan emblemática.